UV Spectrophotometric Method Development and Validation for the Simultaneous Estimation of Antihypertensive Drugs - V. Bhopale, Shubhada; P. Kumar, Mahesh; kshirsagar, Sunil N. (Journal of Neonatal Surgery, 2024)
The present study focuses on the analytical characterization and UV spectrophotometric method validation for two widely used antihypertensive drugs, Olmesartan Medoxomil and Sacubitril Calcium. FTIR spectroscopy confirmed the presence of functional groups such as –OH, C=O, and aromatic rings, indicating the structural integrity of both compounds. DSC analysis revealed sharp melting endotherms at 177.18°C for Olmesartan Medoxomil and 156.96°C for Sacubitril Calcium, confirming their thermal stability and purity. UV spectrophotometric analysis was performed to determine the λmax, which was found to be 255 nm for Olmesartan Medoxomil and 254 nm for Sacubitril Calcium. The method was validated as per ICH guidelines and showed excellent linearity, with correlation coefficients (R²) of 0.9996 and 0.9995 respectively. Accuracy studies revealed percent recoveries close to 100%, while precision, robustness, and ruggedness assessments confirmed method reliability. The low LOD and LOQ values indicate good sensitivity. Overall, the developed method is simple, rapid, precise, and suitable for routine quality control of both drugs in pharmaceutical formulations.